Membangun Startups Incubator Untuk Membentuk Ekosistem Startups Yang Inovatif Dan Kompetitif - Linda Ayu Widyaningrum; Wuliandari Tri Putri; Sugotowikan Sugotowikan; Asep Taryana (Journal Economic Excellence Ibnu Sina, 2024)
The Fourth Industrial Revolution has driven significant changes across various sectors, with startup emerging as key players in the global economy. Despite their immense potential, many startup face significant challenges, including a high failure rate within the first five years of operation. Design Thinking, a human-centered approach, has surfaced as a solution to address these challenges by helping startup understand user needs, identify problems, and create innovative solutions. This study aims to analyse the application of Design Thinking in building an innovative and competitive startup ecosystem. Using a literature review methodology, this research identifies various tested approaches and strategies, as well as the challenges and opportunities faced by startup in implementing Design Thinking. The findings indicate that the application of Design Thinking can enhance a startup's competitiveness by accelerating product innovation and improving responsiveness to market changes. The main challenges include a lack of understanding of the method and limited human resources with the necessary skills in technology and design. We suggest establishing Startups Incubator, with the framework adapted and modified to include active participation from stakeholder. The Startups Incubator will place members as strategic component of socio-economical system; will create a culture of adaptive innovation that is able to solve problems in society, in line with stakeholder needs, market realities and system complexity. By integrating some Startups Incubators, then we can create startups ecosystem that is continuously innovate and market-competitive.